International Model for Policy Analysis of Agricultural Commodities and Trade (IMPACT) Model - Batka, Miroslav; Bhandary, Prapti; Bryan, Elizabeth; Cenacchi, Nicola; De Pinto, Alessandro; Enahoro, Dolapo; Leroy, Laetitia; Li, Man; Magnan, Nicholas; Mason-D’Croz, Daniel; Msangi, Siwa; Nelson, Gerald C.; et al. (International Food Policy Research Institute, 2012)
The IMPACT model is designed to examine alternative futures for global food supply, demand, trade, prices, and food security. The IMPACT model allows IFPRI to provide both fundamental, global baseline projections of agricultural commodity supply, demand, trade, prices and malnutrition outcomes along with cutting-edge research results on quickly evolving topics such as bioenergy, climate change, changing diet/food preferences, and many other themes. IMPACT covers 44 commodities, which account for virtually all of world food production and consumption, including all cereals, soybeans, roots and tubers, meats, milk, eggs, oils, meals, vegetables, fruits, sugar and sweeteners, and fish in a partial equilibrium framework. It is specified as a set of 115 country-level supply and demand equations where each country model is linked to the rest of the world through trade. The model is written in the General Algebraic Modeling System (GAMS) programming language. The solution of the system of equations is achieved using the Gauss–Seidel method algorithm. This procedure minimizes the sum of net trade at the international level and seeks a world market price for a commodity that satisfies market-clearing conditions.